Conflict Situations and Children’s Education in Manipur - Rebecca, N. (JOURNAL OF INDIAN EDUCATION, 2008)
Manipur has been witnessing various forms of conflict for a long period of time and children have been the most vulnerable section to such situations. From the immediate to the long-term effects, children have been the victims of conflicts. The paper tries to understand how situations of conflict in Manipur have seriously impeded the development of children by denying them their basic right to education. It also suggests the possible measures towards ensuring this basic right even in times of conflict situations.